Gaya Skandinavia Pada Ilustrasi Flora Marimekko - Citra Kemala Putri (ArtComm, 2021)
The Scandinavian style is one of the styles that has big influence on the development of interior design, product and visual in the world. The Scandinavian style is influenced by several things including folk culture, as well as local and international historical events. Marimekko is a Finnish and Scandinavian-style pioneered company that was founded in 1951.By today, Marimekko has produced thousands of illustrations which are used as patterns on dresses, home furnishings, etc. The objects those Marimekko's illustrations usually used such as geometric, abstract and floral objects. This study is analizing the influence of the Scandinavian style on the floral illustrations of Marimekko’s pattern illustrations. The case of this study are several Marimekko illustrations entitled "Unikko (Poppy)" and "Maalaisruusuu (Country Roses)" by Maija Isola in 1964, "Ajusko" by Annika Rimala in 1968, "Kuuma (Hot)" by Fujiwo Ishimoto in 1978, “Kylmankukka (Pasque Flower)” by Aino-Maija Metsoia in 2008, “Oodi (Ode)” by Teija Puranen in 2012, and “Hyma (Frost)” by Aino Maija Metsola in 2019 This study uses qualitative method which is supported by various data sources. The results of this study reveal that the way of depicting the illustrations use Naturalist Perspective Momentopname visual language (NPM) dominantly and they contain Scandinavian illustration characteristics. The illustrations used in the Marimekko patterns show a strong character and identity, not only as a brand, but also as cultural identity whch are geographical and communal folk tradition identity.